Revised Ordinances of the City of Victoria Texas, at 75, Revised Penal Ordinances: Discharging Firearms, § 1 (1899) - (:unkn) unknown (My University, 1899)
If any person shall discharge any gun, pistol or firearm of any description on or across any public square, street or alley, or elsewhere within the corporate limits of the City of Victoria, whether the premises on or across which such fire arm is discharged be public or private he shall be fined in any sum not to exceed ten dollars.
Keywords: DISCHARGE